ADAM17 participates in the protective effect of paeoniflorin on mouse brain microvascular endothelial cells. Issue 12 (19th June 2018) - Wang, Haifang; Ma, Shuhui; Li, Jing; Zhao, Miaomiao; Huo, Xueping; Sun, Jingying; Sun, Lijun; Hu, Jun; Liu, Qinshe
Abstract : Paeoniflorin (PF), the most abundant active ingredient of traditional Chinese herbal medicine Paeoniae Radix, has been recognized as a potential neuroprotectant due to its remarkable efficacy on mitigating cerebral infarction and preventing the neurodegenerative diseases. However, the precise mechanisms of PF remain incompletely understood. In this study, we first provided evidence for the protective effect of PF on hydrogen peroxide‐induced injury on mouse brain microvascular endothelial bEnd.3 cells, and for transactivation of the epidermal growth factor receptor (EGFR) signal induced by PF, suggesting that EGFR transactivation might be involved in the beneficial role of PF. Next, by detecting the phosphorylation of a disintegrin and metalloprotease 17 (ADAM17) at Thr 735 and performing loss‐of‐function experiments with the ADAM17 inhibitor and ADAM 17‐siRNA, we showed that PF‐induced transactivation of EGFR and downstream ERKs and AKT signaling pathways were dependent on ADAM17. Furthermore, PF‐induced phosphorylation of ADAM17 and the EGFR transactivation were inhibited by the inhibitors of adenosine A1 receptor (A1R) or Src kinase that were applied to cells prior to PF treatment, implying the involvement of A1R, and Src in the activation of ADAM17. Finally, PF reduced the cell surface level of TNF‐receptor 1 (TNFR1) and increased the content of soluble TNFR1 (sTNFR1) in the culture media, indicating that PF might enhance the shedding of sTNFR1. Taken together, we conclude that A1R and Src‐dependent activation of ADAM17 participates in PF‐induced EGFR transactivation and TNFR1 shedding on mouse brain microvascular endothelial cells, which may contributes to the neuroprotective effects of PF. Abstract : In mouse brain microvascular endothelial cells, paeoniflorin (PF) induces activation of ADAM17, which participates in the PF‐induced epidermal growth factor receptor (EGFR) transactivation and TNFR1 shedding, contributing to the neuroprotective effects of PF.